Criticism of Sharia Supervisory Board Position at Islamic Financial Institution: Evidence from Indonesia - Hardiyono Hardiyono; Dini Maulana Lestari; Reni Furwanti; Ifah Finatri Latiep (Fakultas Ekonomi, UIN Maliki Malang, 2023)
This research aims to analyze and critic the role of Sharia Supervisory Board (SSB) at Islamic Financial Institution. This considered iportant because SSB is a core organization of Islamic Financial Institutions (IFIs) to legitimate and maintan all IFIs’ operational activities that have to appropriate through sharia compliance. Nevertheless, the position of SSB in Indonesia is lack of power and independecy while doing its duties, which absolutely this issue does not accordance through fatwa of National Sharia Council regarding to SSB’s position and funcition. This research criticize the position and function of SSB on sharia audit for IFIs. This is a qualitative research with library method approach. Furthermore, this research delineates, that there is such a decentralization position and function of SSB due to lack of power and decentral position of SSB when carry out its duties regarding to supervising IFIs whether are appropriate through sharia compliance or not. Thus, it requires such a training in order to boost independency of SSB when supervise IFIs.